2021
DOI: 10.2147/vmrr.s324500
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Burden of Small Intestinal Parasitic Helminth in Goats and Sheep Slaughtered at Bishoftu Elfora Export Abattoir (Ethiopia)

Abstract: Purpose: Although helminthiasis have been recognized as health constraints of small ruminants, there was no study conducted to reveal their types and burden in goats and sheep slaughtered at Bishoftu, Ethiopia. Hence, this study is aimed to evaluate the current status of helminth parasites and estimate its burden in study animals. Methods: The study was carried out from November 2016 to April 2017 to identify the species and also to estimate the burden of small intestinal parasitic helminth in goats and sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Numerous GI nematodes belonging to the genera Haemonchus , Trichostrongylus , Oesophagostomum , Bunostomum , Strongyloides , Cooperia , Nematodirus , and Trichuris have been reported in parasitological studies conducted in various parts of the country ( Berhe and Aragaw, 2019 ; Haile et al, 2018 ; Kenea et al, 2015 ). Studies on gastrointestinal parasites of goats from various parts of Ethiopia have revealed a prevalence range of 40%–80% ( Abdo et al, 2017 ; Ayana and Ifa, 2015 ; Hurisa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous GI nematodes belonging to the genera Haemonchus , Trichostrongylus , Oesophagostomum , Bunostomum , Strongyloides , Cooperia , Nematodirus , and Trichuris have been reported in parasitological studies conducted in various parts of the country ( Berhe and Aragaw, 2019 ; Haile et al, 2018 ; Kenea et al, 2015 ). Studies on gastrointestinal parasites of goats from various parts of Ethiopia have revealed a prevalence range of 40%–80% ( Abdo et al, 2017 ; Ayana and Ifa, 2015 ; Hurisa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cestode parasites, monezia species in this study was 13.46% and 13.14% in sheep and goats respectively. This result is not in line with (27) who reported 30.4% and 40% in sheep and goats around Bedele in south-western Ethiopia (22) who reported 26.04% in sheep and 23.81% in goats in and around Wolaita Sodo, (16) who reported 16.13% prevalence of monezia species in goats of Ogaden and (30) reported 52.6% in sheep and47.% in goats slaughtered at Bishoftu Elfora Export Abattoir. The results by the above authors are relatively much higher than the present finding.…”
Section: Resultsmentioning
confidence: 55%
“…Parasitic helminths are responsible for large problems in health parameters, reproducibility, and productivity of sheep, goats, and cattle in Ethiopia (Hernandez and Sanchez, 2014;Huang et al, 2014;Hurisa et al, 2021). Helminths usually cause body weight loss, digestive disturbance, and emaciation (Income et al, 2021;Johansson, 2017;Heinon, 1989;Lamrioui et al, 2013).…”
Section: Overall Prevalence Of Gastrointestinal Helminth Parasite Inf...mentioning
confidence: 99%
“…Gastrointestinal (GI) nematode and trematode (fluke) infections in ruminants cause major problems for both small-and large-scale farmers in the developing world (Huang et al, 2014;Sheferaw et al, 2013). The infection with parasitism causes lower productivity, mortality, and high economic losses, affecting the income of smallholder dairy farming communities (Huang et al, 2014;Income et al, 2021). Ruminants, cattle, goats, and sheep represent an important source of animal protein in many countries worldwide, supplying a high percentage of daily meat and dairy products in cities and villages, including Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation